(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The acclaimed author of ‘Milkman’ and ‘Little Constructions’, Anna Burns, has emerged as a prominent voice in contemporary literature. She is celebrated for her insightful exploration of gender dynamics, power structures, and societal norms. Burns questions conventional gender norms and provides a profound analysis of the complexity of womanhood through her distinctive narrative style and subtle character portrayals. She embodies the ethos of feminism in her novels, navigating themes of female agency, autonomy, and resistance against patriarchal oppression. This paper delves into the intricate writing techniques employed by Anna Burns, focusing primarily on her acclaimed novels ‘Little Constructions’ (2007) and ‘Milkman’ (2018). Through a comprehensive analysis, the intention is to unravel the unique narrative strategies, linguistic devices, and thematic underpinnings that characterizes Burn’s literary style. By exploring her use of stream of consciousness, unreliable narration, and the manipulation of language, this paper illuminates how Burns crafts compelling narratives that captivate readers and offer profound insights into the complex social and psychological landscapes. Anna Burns explores the multifaceted themes such as identity, power-dynamics, political unrest and the impact of societal norms. The purpose of the study is to shed light on Burns' perceptive observations on human experiences and the intricacies of social interaction by analysing the nuanced portrayal of these themes within the context of Northern Ireland.